Issues in Measuring and Interpreting Human Appetite (Satiety/Satiation) and Its Contribution to Obesity - Gibbons, Catherine (Curr Obes Rep, 2019)
PURPOSE OF REVIEW: The goals of this paper are to report current research practices in investigations of human appetite control and to assess their relationships with emerging theoretical principles. Appetite is often distinguished by the separation of homeostatic and hedonic processes. RECENT FINDINGS: This report assesses the validity of a homeostatic toolkit to measure subjectively perceived hunger and its relationship to the developing processes of satiation (control of meal size) and satiety (control of the post-eating period). The capacity of a procedure to measure the influence of hedonic processes on food intake is also evaluated. A major issue is the relationship between the pattern of eating behaviour (influenced by the underlying drive to eat and the inhibition induced by the act of eating itself) and the parallel underlying profile of hormonal and other metabolic biomarkers. SUMMARY: Increasing recognition is being given to individual variability in the expression of appetite, and the fact that the use of the average (mean) response conceals important information about the nature of appetite control. There is a growing interest in the identification of satiety phenotypes that operate in parallel to metabolic phenotypes. Interestingly, energy expenditure (metabolic and behavioural) contributes to an energy balance framework for understanding energy intake (appetite).